ANALISIS KUALITAS LAYANAN DAN KEPUASAN PELANGGAN DI BENGKEL TOYOTA-A2K - Jimmy Irawan; Bobby Oedy P. Soepangkat; Sony Sunaryo (Jurnal Teknobisnis, 2006)
Toyota-A2K auto repair shop, which serves as the center of Toyota authorized after sales service has a mission to support the new cars selling activities by way of providing car treatment and repair services. The service quality within the auto repair shop is ought to be preserved so that the gaps between customers ' perception and expectation can be avoided. The lower the customers ' perception toward the sen•'ice quality than their expectation leads to the customers' dissatisfaction, which then resulted the decrease of customer retention within the overall business cycle. This research designed to measure the customers ' satisfaction level of service quality in Toyota-A2K auto repair shop all the way through five dimensions of service quality; that are tangibles, reliability, responsiveness, assurance, and empathy. The level of customers' satisfaction measured by way of analyzing gap score between customers ' perception and expectation within those five dimensions of service quality.